tìm x
5x + 40 = 25
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có :
\(\frac{3x-1}{40-5x}=\frac{25-3x}{5x-34}\)
\(=>\left(3x-1\right)\left(5x-34\right)=\left(40-5x\right)\left(25-3x\right)\)
\(=>15x^2-102x-5x+34=1000-120x-125x+15x^2\)
\(=>15x^2-107x+34=1000-245x+15x^2\)
\(=>34-107x=1000-245x\)
\(=>1000-245x+107x=34\)
\(=>1000-138x=34\)
\(=>138x=1000-34=966\)
\(=>x=\frac{966}{138}=7\)
=>(2x+3).(10x+2)=(5x+2).(4x+5)
=>(2x.10x)+(2x.2)+(3.10x)+(3.2)=(5x.4x)+(5x.5)+(2.4x)+(2.5)
=>20x2+4x+30x+6=20x2+25x+8x+10
=>20x2-20x2+4x-8x+30x-25x=10-6
=>0+4x-8x+30x-25x=4
=>-4x+30x-25x=4
=>26x-25x=4
=>x=4
B)=>(3x-1).(5x-34)=(40-5x).(25-3x)
=>15x2-102x-5x+34=1000-120x-125x+15x2
=>15x2-107x+34=1000-245x+15x2
=>15x2-15x2-107x+245x=1000-34
=>0-107x+245x=966
=>138x=966
=>x=7
A,=>(2x+3).(10x+2)=(5x+2).(4x+5)
=>(2x.10x)+(2x.2)+(3.10x)+(3.2)=(5x.4x)+(5x.5)+(2.4x)+(2.5)
=>20x2+4x+30x+6=20x2+25x+8x+10
=>20x2-20x2+4x-8x+30x-25x=10-6
=>0+4x-8x+30x-25x=4
=>-4x+30x-25x=4
=>26x-25x=4
=>x=4
\(\frac{3x-1}{40-5x}=\frac{25-3x}{5x-34}\)
=> (3x-1).(5x-34)=(40-5x).(25-3x)
=> 3x.(5x-34)-(5x-34)= 40.(25-3x)-5x.(25-3x)
=> 15x2-102x-5x+34= 1000-120x-125x+15x2
=> 15x2- 107x+34 = 1000-245x+15x2
=> 107x+34 =1000-245x
=> 138x=966
=> x=7
a)11-(15+11)=x-(25-9)
11-26=x-16
-15=x-16
x=-15+16
x=1
vậy x=1
b)2-x=17-(-5)
2-x=22
x=2-22
x=-24
vậy x=-24
c)lxl-7=9
lxl=9+7
lxl=16
=>x=+-16
vậy x=+-16
d)3x-40=5x+32
3x-5x=40+32
(3-5)x=72
-2x=72
x=72:(-2)
x=-36
vậy x=-36
\(P=\frac{2\left(x-2\right)\left(x+2\right)}{x^2+x+5}.\frac{5\left(x^2+x+5\right)}{\left(x-4\right)\left(x+3\right)}.\frac{\left(x-1\right)\left(x-4\right)}{10\left(x-2\right)\left(x+2\right)}=\frac{x-1}{x+3}\)
ĐK: \(x\ne\left\{4;-3;1;2;-2\right\}\)
b, \(P\in Z\Rightarrow\frac{x-1}{x+3}\in Z\Rightarrow x-1⋮\left(x+3\right)\Rightarrow-4⋮\left(x+3\right)\Rightarrow\left(x+3\right)\in\left\{-4;-2;-1;1;2;4\right\}\)
\(\Rightarrow x\in\left\{-7;-5;-4;-2;-1;1\right\}\)
\(\Rightarrow P\in\left\{2;3;5;-3;-1;0\right\}\)
a) \(\frac{2x+3}{5x+2}=\frac{4x+5}{10x+2}\)
\(\Leftrightarrow\)\(\left(2x+3\right)\left(10x+2\right)=\left(5x+2\right)\left(4x+5\right)\)
\(\Leftrightarrow20x^2+4x+30x+6=20x^2+25x+8x+10\)
\(\Leftrightarrow20x^2-20x^2+4x+30x-25x-8x=10-6\)
\(\Leftrightarrow x=4\)
b) \(\frac{3x-1}{40-5x}=\frac{25-3x}{5x-34}\)
\(\Leftrightarrow\left(3x-1\right)\left(5x-34\right)=\left(40-5x\right)\left(25-3x\right)\)
\(\Leftrightarrow15x^2-102x-5x+34=1000-120x-125x+15x^2\)
\(\Leftrightarrow15x^2-15x^2-102x-5x+120x+125x=1000-34\)
\(\Leftrightarrow138x=966\)
\(\Leftrightarrow x=7\)
a ) \(\frac{2x+3}{5x+2}=\frac{4x+5}{10x+2}\)
\(\left(2x+3\right).\left(10x+2\right)=\left(5x+2\right)\left(4x+5\right)\)
\(20x^2+4x+30x+6=20x^2+25x+8x+10\)
\(4x+30x-25x-8x=10-6\)
\(x=4\)
`5x + 40 = 25`
`=> 5x = 25 - 40`
`=> 5x = -15`
`=> x = -15:5`
`=> x = -3`
Vậy ...
5x+40=25
5x=25-40
5x=-15
x=-15:5
x=-3